The making of the modern Iranian woman : gender, state policy, and popular culture, 1865-1946 - Amin, Camron Michael (University Press of Florida, 2002)
''Combining the best of archival research, oral history, and textual analysis ... Amin's text offers new avenues of inquiry into the relationship between modern states and the lives of their female citizens.''--Lisa Pollard, University of North Carolina, Wilmington''An imaginative and well-documented study of the development of modern Iranian womanhood [that] demonstrates the developing nature of the patriarchal obstacles in the way of women's emancipation as much as it reveals the dynamism and complexity of the Women's Awakening.